User studies in archives: overview of experience reports published in national journals Estudios de usuarios en archivos: resumen de informes de experiencias publicados en revistas nacionales - Vitoriano, Marcia Cristina de Carvalho Pazin [UNESP]; Leme, Thalita Fernanda [UNESP]; Casarin, Helen de Castro Silva [UNESP] (My University, 2020)
The article aims to analyze user studies in the Brazilian archival context, considering the reality in archives as information units. The main characteristics of uses and user studies carried out in archives were identi-fied, based on a bibliographic research on experience reports.
Estudos de usuários em arquivos Panorama dos relatos de experiência publicados em periódicos nacionais
Keywords: archival science; private archives; public archives; user studies